Estudios del trabajo desde el Sur, Vol.3 Repensar el sur desde el Estallido - Galliorio, Álvaro; Julián, Dasten (Ariadna Ediciones, 2020)
Analysis of the transformations in the sphere of work in Chile and Latin America. Precarization processes. Immigration and social exclusion